Inertial measurement unit-based real-time feedback gait immediately changes gait parameters in older inpatients: a pilot study - Miyazaki, Takasuke; Kiyama, Ryoji; Takeshita, Yasufumi; Shimose, Daichi; Araki, Sota; Matsuura, Hisanori; Uto, Yuki; Nakashima, Shobu; Nakai, Yuki; Kawada, Masayuki (Frontiers in Physiology, 2024)
The effect of gait feedback training for older people remains unclear, and such training methods have not been adapted in clinical settings. The purpose of this study was to examine whether inertial measurement units (IMUs)-based real-time feedback gait for older inpatients immediately changes gait parameters. Seven older inpatients (mean age: 76.0 years) performed 3 types of 60-s gait trials with real-time feedback in each of the following: walking spontaneously (no feedback trial); focused on increasing the ankle plantarflexion angle during late stance (ankle trial); focused on increasing the leg extension angle, defined by the location of the ankle joint relative to the hip joint in the sagittal plane, during late stance (leg trial). Tilt angles and accelerations of the pelvis and lower limb segments were measured using 7 IMUs in pre-and post-feedback trials. To examine the immediate effects of IMUs-based real-time feedback gait, multiple comparisons of the change in gait parameters were conducted. Real-time feedback increased gait speed, but was not significantly differ in control (p=0.176), ankle (p=0.237) and leg trials (p=0.398).Step length was significantly increased after the ankle trial (p=0.043, r=0.77: large effect size). Regarding changes in gait kinematics, the leg trial increased leg extension angle compared to the no feedback trial (p=0.048, r=0.77: large effect size). IMUs-based real-time feedback gait changed gait kinematics immediately, and suggests the feasibility of a clinical application for overground gait training in older people.